Tolerance Index and Policy Model in Sustainable Tourism Development in Central Lombok Regency, Indonesia - Agus, Agus; Ansori, Zakaria (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article aims to describe the tolerance index and management model of tourism development in Central Lombok Regency. Using the mix-method, this study found that the religious tolerance index information was 3.61 or had a high category. The religious tolerance index is supported by a two-dimensional-based management model, namely regulation and institutional. The regulatory dimension refers to the 2006 Joint Regulation of the Minister of Religion and the Minister of Home Affairs, the 2020-2024 Ministry of Religion Strategic Plan, and the 2021-2026 Lombok Regency RPJMD. Recommended policy development models include; The regulatory dimension is guided by Presidential Regulation Number 58 of 2023, Regulation of the Minister of Religion Number 3 of 2024, and the Central Lombok Regency RPJPD 2025-2045. By referring to these regulations, the institution of tolerance management policy applies the hexa-helix model collaborative management approach, namely policies through the collaboration of six stakeholders which include: local governments; FKUB; the business world; NGOs / religious organizations; mass media; and universities. Local governments play a role in designing and developing policies, while other stakeholders play a supporting role in policy management.